Persepsi Masyarakat Toobuuha Tentang Bahaya Penularan Covid-19 Terhadap Motivasi Vaksin Covid-19 - Dian Yuniar Syanti Rahayu; M. Bustan (STIKes Karya Kesehatan, 2023)
COVID-19 vaccination efforts still cause pros and cons in the community, the main reason for refusal to the COVID-19 vaccine is related to vaccine safety. Public perceptions and motivations for the Covid-19 vaccine vary because public knowledge and understanding regarding the benefits and risks of the Covid-19 vaccine also vary depending on the information they receive. The purpose of the study was to determine public perceptions about the dangers of covid-19 transmission on the motivation of the covid-19 vaccine in Tobuuha Village, Puuwatu District, Kendari City, Southeast Sulawesi Province. The study included descriptive analytics with a cross-sectional study research design. The study population was the target of the general public vaccine in Tobuuha Village as many as 6675 people, a sample of 99 respondents. Statistical test using Chi Square Test. The results showed that most respondents had sufficient perception, namely as many as 61 people (61.6%), most had sufficient motivation, namely as many as 60 people (60.6%) and there was a relationship between public perception of the dangers of covid-19 transmission to the motivation of the covid-19 vaccine (p value = 0.003). Advice to the government for the government to increase socialization and education to the wider community, so that they obtain correct information related to covid-19 vaccination and form positive perceptions and motivations related to covid-19 vaccination